2010
DOI: 10.1161/strokeaha.110.590554
|View full text |Cite
|
Sign up to set email alerts
|

Low Cerebral Blood Volume Is Predictive of Diffusion Restriction Only in Hyperacute Stroke

Abstract: Background and Purpose-Diffusion-weighted MRI (DWI) demonstrates ischemic tissue with high sensitivity. Although low cerebral blood volume (CBV) is also used as a marker for infarction, the quantitative relationship between diffusion abnormalities and CBV is unknown. We tested the hypothesis that CBV would decrease proportionally to the apparent diffusion coefficient in patients with acute stroke and thus could be used as a surrogate parameter for diffusion restriction. Methods-Perfusion-weighted imaging and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For instance, there is evidence that DWI infarct core may have high, low, or normal CBV depending on infarct age. 36 We acknowledge that CTP is not necessarily a criterion standard facilitating "correct" IAT triage with which the stroke scale group's decision should be compared. Our objective was to determine whether triage decisions with and without the use of CTP are analogous, with our hypothesis being that CTP does not significantly alter the triage decision that would have been made by using NIHSS without CTP.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, there is evidence that DWI infarct core may have high, low, or normal CBV depending on infarct age. 36 We acknowledge that CTP is not necessarily a criterion standard facilitating "correct" IAT triage with which the stroke scale group's decision should be compared. Our objective was to determine whether triage decisions with and without the use of CTP are analogous, with our hypothesis being that CTP does not significantly alter the triage decision that would have been made by using NIHSS without CTP.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, the study was semi-qualitative. However, relative PWI parameters are simply obtained and it has been observed that speculated CBV from rCBV is similar to that from volumetric assessment (44). In a previous study by the present authors, using the speculation method, it was revealed that 118% of the contra-, it was revealed that 118% of the contra-it was revealed that 118% of the contralateral CBV appeared in normal perfused patients and 77% in hypoperfused patients within DWI lesions; and surrounding the DWI lesion 121% of the contralateral CBV in normal perfused patients and 90% in hypoperfused patients, respectively; which suggests that >90% of the contralateral CBV may fit the metabolic demands of the hypoperfused tissues, and >120% of the contralateral CBVs may maintain a normal perfusion map (45).…”
Section: Discussionmentioning
confidence: 99%
“…[5, 26, 27]Furthermore, CBV lesions can be reversible and appear to be time dependent. [28] Different CBV thresholds have been suggested for irreversible ischemia, depending on the size of the infarct[5], type of post-processing software[29, 30] or location of the lesion within the white or grey matter. [31] Indeed, there is no agreement yet on definitions and parameters of the ischemic core and penumbra using CTP parameters.…”
Section: Discussionmentioning
confidence: 99%